NURSING RESPONSIBILITIES AND THEIR IMPACT ON OUTPATIENT MATERNAL HEALTHCARE QUALITY (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Outpatient healthcare services for women of reproductive age and pregnant women are considered one of the key components in improving maternal and child health indicators. The quality and effectiveness of these services are strongly influenced by the professional competence and practical activities of nurses working within primary healthcare systems. In contemporary medical practice, nurses function not only as physician assistants but also as independent healthcare professionals responsible for health education, disease prevention, early identification of risk factors, patient counseling, and continuous monitoring. During pregnancy, nurses maintain consistent communication with women, organize antenatal and postnatal follow-up, encourage participation in screening and preventive examinations, and provide recommendations regarding medication use, nutrition, hygiene, and healthy lifestyle behaviors. In addition, nursing interventions support the timely registration of pregnant women, facilitate early detection of complications, and strengthen psychological assistance, thereby improving the continuity and overall quality of outpatient medical care. This article examines the professional role and functional responsibilities of nurses in ambulatory healthcare, with particular attention to their contribution to safe pregnancy monitoring, enhancement of healthcare quality, and promotion of reproductive health.
Keywords: Outpatient healthcare, nursing practice, reproductive health, pregnant women, antenatal services, postnatal follow-up, primary healthcare, preventive care, health education, patient counseling, maternal health, child health.